The Influence of Hydrogeological Conditions on Salt Quality Standards In Ambal District, Kebumen Regency, Central Java - Radityo, Daniel; Pratomo, Septyo Uji (Jambura Geoscience Review, 2024)
Salt (NaCl), also known as halite, has a vital role as an essential ingredient in human life and industry. Kebumen Regency in Central Java, especially along the south coast in Ambal District, is one of the area in Indonesia that produces salt, originating from elongated dome-shaped salt ponds, which are the primary source of salt production in the region. Salt quality standards are regulated by SNI 3556:2016, which provides limits for metal contamination such as cadmium (Cd) 0.5 mg/kg, lead (Pb) 10 mg/kg, mercury (Hg) 0.1 mg/kg, and arsenic (As) 0.1 mg/kg. The conditions of seawater and groundwater used in the salt production process have a significant impact on the quality of the salt produced, which can be determined from hydrogeological studies. The results of measuring residents' wells at 43 points show that the depth of the groundwater level ranges from 4.4 to 14.75 meter below sea level. The results of salt analysis from 2 different salt ponds showed Cd levels ranging between 0.0949—0.1001 mg/kg, Pb between 0.5163—0,755 mg/kg, Hg between 0.01198—0.06203 mg/kg, and negative As levels; with water content ranging from 14.43-14.92% w/w and NaCl content between 72.3-85.8%. The analysis of well water and seawater from 3 samples showed Cd 0.0009 mg/kg, Pb 0.0011-0.0098 mg/kg, Hg 0.0001 mg/kg, and As 0.001 mg/kg. The results of groundwater level mapping show that hydrogeological conditions influence the quality standards for salt on the southern coast of Kebumen, especially by the significant grain size factor that carries groundwater and the elements dissolved in it. Meanwhile, salt produced from 2 salt ponds in Ambal District did not meets quality standards based on SNI 3556:2016.